Carfilzomib Induced Tumor Lysis Syndrome and Other Adverse Events. (April 2020) - Sandy, El Bitar; Weerasinghe, Chanudi; Terjanian, Terenig
In the area of multiple myeloma (MM) therapy, proteasome inhibitors (PI) have emerged with promising responses both in the first- and second-line setting. Carfilzomib (CFZ) is a second-generation, selective PI approved in 2012 for the treatment of relapsed/refractory multiple myeloma (RRMM) in patients who received 2 prior therapies or have evidence of disease progression within 60 days of completion of last therapy. Its safety profile reported adverse events (AEs) ranging from drug-related AEs (nausea and vomiting), hematologic AEs (neutropenia and thrombocytopenia), and nonhematologic AEs (electrolyte imbalances). As CFZ use is gaining popularity, various hematological, renal, cardiovascular, pulmonary, and neurological toxicities have been reported. We are presenting this case to describe a rare occurrence of tumor lysis syndrome (TLS) with the use of this novel targeted therapy.